2022
DOI: 10.2196/39309
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Implementation of a Text Messaging Intervention to Reduce Depression and Anxiety Symptoms Among Latinx and White Adults During the COVID-19 Pandemic

Abstract: Background SMS text messaging interventions are increasingly being used to help people manage mental health symptoms due to the COVID-19 pandemic. Despite the widespread adoption of SMS text messaging interventions, little is known about racial and ethnic differences in effectiveness, feasibility, and implementation factors. Objective A hybrid type 1 mixed-methods study was conducted to compare the effectiveness and implementation of the StayWell interv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our prior work with the StayWell at Home program indicated that the intervention was associated with overall reductions in depression and anxiety symptoms as rated by the PHQ and GAD [ 7 , 8 ]. Here, we extend those findings to the outcome of daily mood ratings to better understand continuous symptom fluctuations at the daily level and to develop the evidence of text-messaging programs for supporting mental health outcomes among diverse communities disproportionately affected by the COVID-19 pandemic [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our prior work with the StayWell at Home program indicated that the intervention was associated with overall reductions in depression and anxiety symptoms as rated by the PHQ and GAD [ 7 , 8 ]. Here, we extend those findings to the outcome of daily mood ratings to better understand continuous symptom fluctuations at the daily level and to develop the evidence of text-messaging programs for supporting mental health outcomes among diverse communities disproportionately affected by the COVID-19 pandemic [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of text messages and collection of self-reported mood ratings was conducted via a HIPPA-compliant platform, HealthySMS. The University of California Berkeley Institutional Review Board reviewed and approved all study procedures [ 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations